Complexity and the art of education: A study of how to approach teaching more challenging engineering systems development concepts - Barker, Stephen G. (The International Academic Forum (IAFOR), 2021)
As the demand for ever more capable products increases, so too does the inherent complexity of the product itself in order to facilitate increased functionality. This is broadly true of products of all sizes, from mobile phones to automobiles to large infrastructure projects. This increased complexity makes specification, design, development and implementation more difficult to understand and achieve, potentially making the process and nature of product development more difficult to teach. There are a number of pedagogical factors to this, including the complexity of the subject, the ability of available teaching methods and technology to communicate and provide coverage of the topic, and the educational preferences of the students involved. This paper considers this issue through the prism of the design of a new masters-level course on complex engineering systems. Literature is analysed to study the nature of complexity in engineering systems development and the challenges it causes, and what mix of taught and experiential-learning might be most appropriate. Experience in delivering courses to masters students is also taken into account to gauge from an andragogical perspective what teaching methods have previously been successful in communicating subject matter that is for some difficult to understand. Feedback from students past and present is analysed to understand how different preferences affect the ability to understand more complex topics, in an attempt to assess how different students respond to different teaching methods. This analysis is used to propose an approach to enhance the education of complex systems design and development for masters students.
Keywords: Complexity; Pedagogy; Engineering